Rapid Glucocorticoid Receptor-Mediated Inhibition of Hypothalamic–Pituitary–Adrenal Ultradian Activity in Healthy Males - Russell, Georgina M.; Henley, David E.; Leendertz, Jack; Douthwaite, Jennie A.; Wood, Susan A.; Stevens, Adam; Woltersdorf, Wolfram W.; Peeters, Bernard W. M. M.; Ruigt, Ge S. F.; White, Anne; Veldhuis, Johannes D.; Lightman, Stafford L. (The Journal of neuroscience, 2010)
A complex dynamic ultradian rhythm underlies the hypothalamic–pituitary–adrenal (HPA) circadian rhythm. We have investigated in normal human male subjects the importance, site of action, and receptor-mediated processes involved in rapid basal corticosteroid feedback and its interaction with corticotrophin releasing hormone (CRH) drive. Pro-opiomelanocortin (POMC), ACTH, and cortisol were measured every 10 min from healthy males during the awakening period or late afternoon using an automated blood sampling system. Mathematical modeling into discrete pulses of activity revealed that intravenous infusion of the synthetic mixed glucocorticoid/mineralocorticoid agonist prednisolone produced rapid inhibition of ACTH and cortisol pulsatility within 30 min in the morning and afternoon. Any pulse that had commenced at the time of injection was unaffected, and subsequent pulsatility was inhibited. Prednisolone also inhibited ACTH and cortisol secretion in response to exogenous CRH stimulation, inferring rapid feedback inhibition at the anterior pituitary. Circulating POMC peptide concentrations were unaffected, suggesting that the rapid corticosteroid inhibitory effect specifically targeted ACTH secretion from pituitary corticotrophs. Prednisolone fast feedback was only reduced by glucocorticoid receptor antagonist pretreatment and not by mineralocorticoid receptor antagonism, suggesting a glucocorticoid receptor-mediated pathway. The intravenous prednisolone suppression test provides a powerful new tool to investigate HPA abnormalities underlying metabolic and psychiatric disease states.